أثر تطبيق نموذج القيمة العادلة في القياس المحاسبي على الابلاغ المالي - حديدي, آدم (Recherches économiques et managériales, 2018)
تهدف هذه الورقة البحثية إلى بيان أثـر استخدام محاسبة القيمة العادلة على الخصائص النوعية للمعلومات المحاسبية وبالتالي على الإبلاغ المالي في القوائم المالية للبنوك، كما أن الدراسة تسعى إلى اكتشاف فيما إذا كانت البيئة المحاسبية الجزائرية توفر متطلبات تطبيق محاسبة القيمة العادلة، ولتحقيق هذه الأهداف تم إعداد إستبانة لتحديد أثر تطبيق محاسبة القيمة العادلة على الإبلاغ المالي في البنوك التجارية الجزائرية . الكلمات المفتاحية : القيمة العادلة، الملاءمة، الموثوقية، الإبلاغ المالي، البنوك التجارية الجزائرية . Abstract : This study aimed to demonstrate the impact of fair value accounting on the qualitative characteristics of accounting information and thus on financial reporting financial statements of banks. The study also sought to discover whether the Algerian accounting environment provides the available requirement of fair value accounting application, To achieve these goals, a questionnaire has been prepared to determine the impact of fair value accounting application on the financial reporting of financial statements in Algerian . Key words : Fair value, pertinence, reliability, financial reporting, Algerian commercial banks commercial banks .